Outcomes of prednisone-tapering regimens for cardiac sarcoidosis: A retrospective analysis demonstrating a benefit of infliximab. (November 2022) - Judson, Marc A.; Adelstein, Evan; Fish, Kenneth M.; Feustel, Paul J.; Yucel, Recai; Preston, Sara; Vancavage, Rachel; Chopra, Amit; Steckman, David A.
Abstract: Background: The optimal treatment strategy for cardiac sarcoidosis has not been standardized. We examined the effectiveness of three prednisone-tapering treatment regimens for cardiac sarcoidosis. Methods: We retrospectively reviewed prednisone-tapering treatment regimens for cardiac sarcoidosis that contained prednisone alone (P), prednisone plus methotrexate (P-M), and prednisone plus infliximab containing regimens (P–I). We defined the success of each regimen as the ability to lower the daily prednisone dose to 7.5 mg or less for 6 or more months without developing an adverse cardiac event. We also examined the lowest effective daily prednisone dose achieved without developing an adverse cardiac event. Results: We identified 61 treatment regimens in 33 cardiac sarcoidosis patients that were analyzed. The success rate of prednisone-tapering regimens was significantly different P: 8/30, 27%; P-M: 3/23, 13%; P–I: 6/8, 75%., p = 0.04. The lowest effective daily prednisone dose for the regimens was also significantly different: P: 14.1 ± 10.1 mg; P-M: 16.9 ± 9.4 mg; infliximab: 7.8 ± 4.9 mg, (p = 0.03); by both measures the success was greatest with the P–I regimen. Conclusions: For the treatment of cardiac sarcoidosis, prednisone-tapering regimens containing infliximab are superior to those containing prednisone alone or prednisone plus methotrexate in terms of reaching 7.5 mg/day of prednisone for more than 6 months and achieving the lowest effective prednisone. Highlights: According to your website and this submission page. Highlights are only needed for reviews. This manuscript is not a review article.